2010
DOI: 10.1586/epr.10.85
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of total membranes and subcellular membranes

Abstract: Membrane proteins are key molecules in the cell and are important targets for drug development. Much effort has, therefore, been directed towards research of this group of proteins, but their hydrophobic nature can make working with them challenging. Here we discuss methodologies used in the study of the membrane proteome, specifically discussing approaches that circumvent technical issues specific to the membrane. In addition, we review several techniques used for visualization, qualification, quantitation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 91 publications
0
15
0
Order By: Relevance
“…These abnormal electrophoretic mobility patterns of particular proteins cause a certain degree of 2D streaking, which can be minimized by (i) decreasing the total amount of protein loading; (ii) using very large gel systems with a higher discriminatory capacity and/or (iii) applying optimized pre-fractionation techniques to decisively decrease sample complexity [95,96,97,98]. Artifacts can be kept to a minimum using 50 to 200 μg of total protein in first dimension gels.…”
Section: Cataloguing Of the Skeletal Muscle Proteome Using Two-dimmentioning
confidence: 99%
“…These abnormal electrophoretic mobility patterns of particular proteins cause a certain degree of 2D streaking, which can be minimized by (i) decreasing the total amount of protein loading; (ii) using very large gel systems with a higher discriminatory capacity and/or (iii) applying optimized pre-fractionation techniques to decisively decrease sample complexity [95,96,97,98]. Artifacts can be kept to a minimum using 50 to 200 μg of total protein in first dimension gels.…”
Section: Cataloguing Of the Skeletal Muscle Proteome Using Two-dimmentioning
confidence: 99%
“…Numerous efforts have been made to improve the solubility and enrichment of membrane proteins during sample preparation. Several comprehensive studies recently covered the commonly used technologies in membrane proteomics and different strategies that circumvent technical issues specific to the membrane (Gilmore and Washburn, 2010; Griffin and Schnitzer, 2011; Groen and Lilley, 2010; Helbig et al, 2010; Weekes et al, 2010). Recently, Sun et al .…”
Section: Sample Preparationmentioning
confidence: 99%
“…Numerous efforts have been made to improve the solubility and enrichment of membrane proteins during sample preparation. Several comprehensive studies recently covered the commonly used technologies in membrane proteomics and different strategies that circumvent technical issues specific to the membrane (Gilmore and Washburn, 2010;Griffin and Schnitzer, 2011;Groen and Lilley, 2010;Helbig et al, 2010;Weekes et al, 2010). Recently, Sun et al reported using 1-butyl-3-methyl imidazolium tetrafluoroborate (BMIM BF4), an ionic liquid (IL), as a sample preparation buffer for the analysis of integral membrane proteins (IMPs) by microcolumn reversed phase liquid chromatography (3RPLC)-electrospray ionization tandem mass spectrometry (ESI-MS/MS).…”
Section: Membrane Proteinsmentioning
confidence: 99%